The Functional Approach in Teaching Arabic Grammar to Develop Grammatical Thinking Skills for Middle School Students in Malaysia/ المدخل الوظيفي في تدريس النحو العربي بتنمية مهارات التفكير النحوي لطلاب المرحلة المتوسطة في ماليزيا - Rana Adel Almousa; Mohd Firdaus Yahaya (Ijaz Arabi Journal of Arabic Learning, 2026)
This study aims to develop an educational strategy focused on teaching grammatical rules through their application in real-life and practical contexts. This approach emphasizes how students use grammar in daily communication and functional tasks, applying it rather than memorizing rules theoretically without practical implementation. Herein lies the role of this approach, alongside grammatical thinking skills, leading to reasoning, in simplifying and facilitating the learning of the Arabic language for Malaysian non-native speakers. The study employed both quantitative and qualitative methodologies. The quantitative method involved distributing a questionnaire to 30 intermediate-level students at Al-Turath Institute for the first semester of the 2024-2025 academic year. Additionally, an achievement test was administered to a sample of 140 intermediate students – comprising a control group of 70 students from Rabat Al-Mustafa Study Center and an experimental group of 70 students from Mahad Tahfiz Al-Turath Negeri Pahang, using pre-test and post-test assessments. The qualitative methodology involved a descriptive analysis of the Ajrumiyyah grammar text, examining how the text presents grammar rules, utilizes them in daily life, and builds reasoning skills.The study's results confirmed the effectiveness of the functional approach in teaching grammar by developing grammatical thinking skills leading to grammatical reasoning. The results also demonstrated the effective and positive role of this approach in shifting from theory to application and enhancing students' analysis and reasoning skills, thereby contributing to the improvement of students' linguistic proficiency in both conversation and writing. The study recommends adopting this approach in the educational process.